The Prevalence of Different Blood Pressure Levels among Adolescents and Young Adults Depending on their Body Weight - Maxmudjanovna, Xashimova Zamira; Soliyevich, Mamasoliyev Nematjon; Xasanboyevich, Tursunov Xatam; Rustambekovna, Kurbanova Rano (American Journal of Bioscience and Clinical Integrity, 2024)
Objective: To study the prevalence of various blood pressure (BP) levels among adolescents and young adults depending on their body weight. Materials and methods: The study involved 2502 participants, including 1371 adolescents and 1131 young adults. Participants were divided into groups based on their body weight: normal weight, overweight, and obesity. Blood pressure was measured using standard methods, and the results were classified according to international guidelines. Statistical analysis was conducted to identify the relationship between body weight and BP levels. Results: The results showed that elevated blood pressure is more common among adolescents and young adults with overweight and obesity compared to those with normal weight. The frequency of hypertension was significantly higher in the overweight and obesity groups. Conclusion: Body weight is a significant risk factor for the development of arterial hypertension among adolescents and young adults. Measures to control body weight are necessary to reduce the risk of hypertension in this age group.